Deciphering the Relationship Between the Trough Concentration of Posaconazole and Its Efficacy and Safety in Chinese Patients With Hematological Disorders - Jia, Meng-Meng; Zhang, Qi-Wen; Qin, Zi-Fei; Lu, Run-Qing; Tian, Xue-Ke; Yang, Jing; Zhang, Xiao-Jian (Frontiers in Pharmacology, 2020)
Posaconazole (PCZ) is effective in preventing and salvage treatment invasive fungal infections in patients with hematologic disorders. However, PCZ displays highly variable individual pharmacokinetics affecting its efficacy and safety. To investigate the correlation between PCZ concentration and efficacy and safety, the following key influencing factors were explored. A total of 285 trough plasma concentrations (Cmin) of 81 Chinese patients receiving PCZ oral suspension for prophylaxis or treatment of invasive fungal infections were collected in this study. The relationships between Cmin values and clinical response and hepatotoxicity were investigated as well as the incidence of clinical response under different Cmin values of PCZ with a logistic regression model. The concentration of PCZ showed remarkable differences among patients with haematologic disorders. PCZ Cmin values of 0.76 µg/mL and 1.0 µg/mL were both associated with an over 80% probability of successful response to prophylaxis and treatment of fungal infections, respectively. No association between Cmin values and hepatotoxicity was noted (P > 0.05). Gender, albumin and co-administration of proton pump inhibitor (PPI) were identified as independent factors influencing PCZ Cmin by multiple linear regression analysis. Furthermore, patients’ C-reactive protein (CRP), albumin, and co-administration of PPI exhibited significant effects on the therapeutic window of patients receiving PCZ for prophylaxis. The plasma concentration is closely associated with therapeutic efficacy of PCZ. It is necessary to adjust the dosing regimens based on PCZ Cmin to obtain an optimal therapeutic response.